About electroexcitation of nuclei with due regard for meson exchange currents - V. K. Tartakovsky; A. V. Fursayev (Ядерна фізика та енергетика)
The reduced probability of the magnetic dipole transition in the 12С nucleus and the corresponding angular distribution of inelastically scattered electrons under excitation of the 1+ nuclear level with the energy of 15,1 MeV have been calculated with due regard for meson exchange currents. An agreement with experimental data is achieved under the condition that the many-particle shell model with intermediate coupling is used.